Factors Influencing Employee Performance Post-COVID-19: Evidence from Service Industry Employees in Indonesia - Budiyanto Budiyanto; Okto Aditya Suryawirawan; Suhermin Suhermin; Abdul Talib Bon (Cita Konsultindo Research Center, 2023)
Ongoing research on employee performance provides valuable insights for organizations seeking to enhance productivity and employee development. Understanding employee performance factors can enable companies to adopt effective strategies and best practices to achieve continuous improvement and optimize organizational success. This study aims to analyze the factors that might influence employee performance in the service industry. Random sampling was used, and 122 respondents were collected using Google Forms. Results were analyzed using partial least square through SmartPLS. Discipline has a positive significant effect on employee performance. Motivation has a positive significant effect on discipline. Motivation has a negative significant effect on employee performance. Career development has a positive significant effect on discipline. Career development does not affect employee performance. Discipline partially and competitively mediated the relationship between motivation and employee performance. Discipline fully mediated the relationship between career development and employee performance. This study provides implications towards company policies related to increasing employee performance.